1994
DOI: 10.1523/jneurosci.14-03-01655.1994
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin immunoreactivity is contained in one physiological cell class in the rat rostral ventromedial medulla

Abstract: Neurons in the rostral ventromedial medulla (RVM) are the major source of serotonergic projections to the dorsal horn. A large body of evidence implicates RVM serotonergic neurons in the modulation of spinal nociceptive transmission. Three physiological classes of RVM neurons, on, off, and neutral cells, are postulated to have different nociceptive modulatory effects on spinal nocifensor reflexes. This study was undertaken to determine which RVM cell class(es) contains 5- HT. In anesthetized rats, RVM neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
80
2
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 45 publications
9
80
2
1
Order By: Relevance
“…Together, such studies led to the reason-able assumption that the RVM provided descending serotonergic pain modulation from the RVM. However, attempts to determine whether either the on-cells or off-cells of the RVM are serotonergic led to the realization that other, nonserotonergic neurons from the RVM may modulate pain (73). In a study of 25 identified RVM neurons, none of the on-cells (i.e., 8 neurons) or off-cells (i.e., 9 neurons) expressed 5-HT, and only 4 out of 8 neutral cells were labeled with 5-HT (73).…”
Section: Descending Serotonergic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, such studies led to the reason-able assumption that the RVM provided descending serotonergic pain modulation from the RVM. However, attempts to determine whether either the on-cells or off-cells of the RVM are serotonergic led to the realization that other, nonserotonergic neurons from the RVM may modulate pain (73). In a study of 25 identified RVM neurons, none of the on-cells (i.e., 8 neurons) or off-cells (i.e., 9 neurons) expressed 5-HT, and only 4 out of 8 neutral cells were labeled with 5-HT (73).…”
Section: Descending Serotonergic Pathwaysmentioning
confidence: 99%
“…However, attempts to determine whether either the on-cells or off-cells of the RVM are serotonergic led to the realization that other, nonserotonergic neurons from the RVM may modulate pain (73). In a study of 25 identified RVM neurons, none of the on-cells (i.e., 8 neurons) or off-cells (i.e., 9 neurons) expressed 5-HT, and only 4 out of 8 neutral cells were labeled with 5-HT (73). Moreover, only 20% of RVM neurons were found to be serotonergic (74), and most of the spinal projections from the RVM are either glycinergic or GABAergic.…”
Section: Descending Serotonergic Pathwaysmentioning
confidence: 99%
“…OFF cells are inhibited by noxious stimulation and excited by opioids, whereas ON cells are excited by noxious stimulation and inhibited by opioids. Both cell types are nonserotonergic (Potrebic et al, 1994;Mason, 1997;Gao and Mason, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological classification of RVM neurons into so-called "on" (i.e., pain facilitatory) and "off" (pain inhibitory) cell groups surprisingly did not include 5HT neurons (Potrebic et al, 1994;Mason, 1997;Gao and Mason, 2000). Rather, serotonergic neurons constitute a heterogeneous population, with slow, regular discharge patterns and variable responses to noxious stimuli and to opioid agonists (Gao and Mason, 2001;Zhang et al, 2006).…”
mentioning
confidence: 97%
“…Comparable conclusions were made from studies in the rat (Porreca et al, 2002;Suzuki et al, 2004b). For example, although intrathecal injection of relatively non-selective 5HT receptor antagonists reduces the analgesia induced by chemical or electrical stimulation of the RVM (Hammond and Yaksh, 1984;Jensen and Yaksh, 1984;Barbaro et al, 1985), studies using more selective antagonists demonstrated that descending 5HT systems can exert both inhibitory or facilitatory actions on nociceptive processing via the 5HT1A and 1B/D receptors or the 5HT1A, 2A, and 3 receptors, respectively (Green et al, 2000;Zeitz et al, 2002;Sasaki et al, 2006).Electrophysiological classification of RVM neurons into so-called "on" (i.e., pain facilitatory) and "off" (pain inhibitory) cell groups surprisingly did not include 5HT neurons (Potrebic et al, 1994;Mason, 1997;Gao and Mason, 2000). Rather, serotonergic neurons constitute a heterogeneous population, with slow, regular discharge patterns and variable responses to noxious stimuli and to opioid agonists (Gao and Mason, 2001;Zhang et al, 2006).…”
mentioning
confidence: 99%